Ambarzumian theorem for quantum graphs with magnetic potential - Brolin, Alice (MATHEMATICA SCANDINAVICA, 2025)
A Schrödinger operator on a metric graph is isospectral to the Laplacian if and only if the potential is zero. This result is extended to the case of magnetic Schrödinger operators. We show that if a magnetic Schrödinger operator is isospectral to the Laplacian then the magnetic potential can be eliminated. Even the case of delta couplings at the vertices is considered.